Deep sequencing reveals high bacterial diversity and phylogenetic novelty in pit mud from Luzhou Laojiao cellars for Chinese strong-flavor Baijiu. (December 2017) - Liu, Mao-Ke; Tang, Yu-Ming; Guo, Xiao-Jiao; Zhao, Ke; Tian, Xin-Hui; Liu, Ying; Yao, Wan-Chun; Deng, Bo; Ren, Dao-Qun; Zhang, Xiao-Ping
Abstract: The pit mud (PM) in fermentation cellar is a complex ecosystem that hosts diverse microbial communities that contribute to the production of Chinese strong-flavor Baijiu (CSFB). However, the microbial ecology of PM, particularly the extent of their phylogenetic novelty remains poorly understood. Here we conducted Illumina MiSeq sequencing to explore the diversity and novelty patterns of PM bacterial communities from Luzhou Laojiao cellars in use for 40 and 400 years. High diversity indices were found in the PM with 16 phyla and 105 genera. Interestingly, the compositions of dominant genera of the PM were significantly different than that reported previously for PM sampled from other geographic sites, suggesting greater microbial diversity of PM. The dominant genus of Caproiciproducens, a caproic acid-producing bacterium, is the first reported for Chinese Baijiu production. Our results demonstrate that the PM hosts a large number of novel taxa, with 26% of the total OTUs (operational taxonomic units) distant to cultured counterparts. The class Clostridia within Firmicutes presented the highest proportion of novel OTUs. Most novel OTUs were initially isolated from diverse environments, the most abundant of which came from Chinese Baijiu brewing ecosystems, highlighting the huge culturing gap within the PM, but at the same time suggesting the importance of these OTUs in CSFB production. The data presented in this study significantly increases the number of bacteria known to be associated with CSFB production and should help guide the future exploration of microbial resources for biotechnological applications. Graphical abstract: Highlights: Bacterial diversity and phylogenetic novelty in pit mud of Chinese Baijiu are revealed by NGS. Eleven genera that play key roles in Baijiu production are identified. 26% of the total taxa presented novel bacterial species. Clostridia are the taxon with the highest proportion of novel sequences.